Primordial memory of the discovery of Brazil in the Brazilian population: The content of school textbooks - Oliveira, Denize Cristina (2004)
This article synthesizes the results concerning knowledge transmission on the discovery of Brazil in the Brazilian school manuals. The fact that this kind of information is received by the students in a systematic way and starting from early age, contributes decisively to configure more than knowledge, something as a primordial memory of such important historical event. The methodology used in this study consisted of content analysis of the content of chapters of nine school manuals used in the fundamental and medium public teaching in Brazil, relatively to the period that precedes the discovery of Brazil until the colonization. The analysis of the texts was done through the technique of co-occurent lexeme analysis in simple text, using the Alceste 4.5 software. Four corpus of text were analysed: the first contained the group of all of the texts; the remaining three were composed, respectively, by texts of the historical period of pre-discovery, of the discovery and of post-colonialism. The result of the analysis of this group of texts reveals the segmentation of its content in five thematic classes: the first inhabitants of the new earth; the Portuguese expansionism; the European trade and the search of new commercial routes; the European marine expansion, the organization of Europe in terms of politics, society and economy. In the corpus of the period of the discovery four thematic classes are observed: the intentionality of Cabral's voyage; the everyday life of the indigenous people; the arrival of the Portuguese and the wealth of the new earth; the power over the people through writing and technology. In the corpus relative to the period of post-discovery six classes were observed: the white ethnocentrism; the pre-colonial period; the hereditary "capitanias"; the black slavery in Brazil; the Portuguese colonial exploration; the dominance and the indigenous acculturation. In the four analyses results point out, with structuring effects for the memory of the discovery, two central themes: the Portuguese and European commercial themes and the indigenous theme. The results also reveal a common orientation among the authors of the different manuals, a result that can state the homogeneity frequently marked of the primordial memory. This homogeneity is characterized by a factual narrative with few analysis of the processes and historical facts; a defence positioning of the explored subjects, above all of the Indians; the privilege to an economical-commercial perspective of the discovery of Brazil, in detriment of a human and social vision of the same process. To conclude, the texts analyzed emphasize the negativity of colonization, such as expressing a critical vision of the treatment given by the colonizers to the Indians and black people, of the economical exploration and of the cultural imposition. Nevertheless, these same texts still emphasize the European enterprising character in this period of navigations and of colonial expansion. DOI: http://dx.doi.org/10.17575/rpsicol.v17i2.450